A Cross-cultural Comparison of Gender Role Portrayal in Magazine Advertisements between China and the UK - Zhang, Yimai (2011)
ABSTRACT This content analysis aims at investigating the similarities and differences in gender role portrayal between Chinese and British magazine advertising. Gender role is examined from six aspects in the current study: age of models, product category and product price, traditional roles, social status, credibility and sexism of models. A total number of 754 Magazine advertisements were coded. The results indicated gender stereotypes in magazine advertising still exist in both China and the UK. In both countries, men were portrayed to be older, more independent, more credible but less sexy than women. The products advertised by male models were more expensive than goods advertised by female characters. Men were more frequently portrayed in occupational roles whereas women were more often depicted in non-occupational roles. Differences on gender role portrayals were also revealed. Chinese females were displayed most frequently in independent images while British women were more often described to be decorative. Differed from Chinese males, more British men were depicted in non-occupational roles than in occupational roles.